ECO-BRANDING AND SUSTAINABLE PLASTIC WASTE MANAGEMENT FOR LOCAL ECONOMIC DEVELOPMENT: EMPOWERING PKK COMMUNITIES IN KELURAHAN GUMURUH, BANDUNG, INDONESIA - simarmata, andriano; Amalia, Friska; Suliastuti, Iftika; Dea Sabiella, Imanda (Bina Nusantara University, 2026)
Plastic waste has become one of the most urgent environmental challenges, particularly at the household level where waste management practices remain limited and underutilized. This community service project was carried out to empower PKK as Family Welfare Empowerment community groups from Kelurahan Gumuruh, Bandung, Indonesia, by integrating eco-branding strategies into sustainable plastic waste management. The main objective was to transform household plastic waste into value-added products that could strengthen community-based economic independence. The method applied was participatory action through design workshops in which 40 PKK participants were actively involved. They were guided by design lecturers and supported by students in generating ideas, developing concepts, and producing product prototypes. A total of 30 prototypes were successfully produced and curated, reflecting both functional and aesthetic qualities, as well as the principles of eco-branding. These products are planned to be exhibited and marketed through local bazaars, providing visibility and potential economic opportunities for the community. The results demonstrated that collaboration between PKK communities and academic facilitators significantly improved participants’ knowledge, creativity, and confidence in plastic waste management. In conclusion, this program highlighted the importance of community and academic partnerships in addressing environmental issues while simultaneously fostering local economic development.